2022
DOI: 10.1111/jog.15258
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean scar pregnancy with expectant management

Abstract: Aim This study aimed to ascertain whether the lower anterior myometrial thickness (MT) between the bladder and the gestational sac in early pregnancy can be used to predict clinical outcomes in women with cesarean scar pregnancy (CSP) after expectant management. Methods We retrospectively analyzed the clinical data and early pregnancy ultrasound images of 21 patients who received expectant management for CSP. Among them, 11 patients with serious complications during pregnancy, such as intraoperative blood loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In these women, 73% hemorrhaged with an estimated blood loss (EBL) ≥1000 ml, and 55% required blood products. Other case series have reported similar results [13,14].…”
Section: Expectant Managementsupporting
confidence: 66%
“…In these women, 73% hemorrhaged with an estimated blood loss (EBL) ≥1000 ml, and 55% required blood products. Other case series have reported similar results [13,14].…”
Section: Expectant Managementsupporting
confidence: 66%
“…Myometrial thickness has been proven to be a prognostic marker [ 17 ]. A study by Fu et al (2022) showed that in the first-trimester scan, the optimal cut-off for myometrial thickness was 3.3 mm, being associated with severe forms of PAS in patients with CSP [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective study of Fu et al 27 evaluated the performance of the RMT measured between the bladder and the gestational sac in early pregnancy in predicting clinical outcome in 21 patients who received expectant management for CSP. Patients were classified into two groups: those who experienced serious complications during pregnancy, such as intraoperative blood loss ≥ 1000 mL or placenta increta or percreta (n = 11), and those without serious complications during pregnancy (n = 10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The retrospective study of Fu et al 27 . evaluated the performance of the RMT measured between the bladder and the gestational sac in early pregnancy in predicting clinical outcome in 21 patients who received expectant management for CSP.…”
Section: Introductionmentioning
confidence: 99%